Clinical studies in restorative dentistry: New directions and new demands. Issue 1 (January 2018) - Opdam, N.J.M.; Collares, K.; Hickel, R.; Bayne, S.C.; Loomans, B.A.; Cenci, M.S.; Lynch, C.D.; Correa, M.B.; Demarco, F.; Schwendicke, F.; Wilson, N.H.F.
Abstract: Clinical research of restorative materials is confounded by problems of study designs, length of trials, type of information collected, and costs for trials, despite increasing numbers and considerable development of trials during the past 50 years. This opinion paper aims to discuss advantages and disadvantages of different study designs and outcomes for evaluating survival of dental restorations and to make recommendations for future study designs. Advantages and disadvantages of randomized trials, prospective and retrospective longitudinal studies, practice-based, pragmatic and cohort studies are addressed and discussed. The recommendations of the paper are that clinical trials should have rational control groups, include confounders such as patient risk factors in the data and analysis and should use outcome parameters relevant for profession and patients.